See-and-Treat Approaches to Cervical Cancer Prevention for HIV-Infected Women - Chibwesha, Carla J. (Curr HIV/AIDS Rep, 2011)
Cervical cancer remains the second commonest cancer among women worldwide, and more than 85% of the global burden of this disease occurs in the developing world. HIV-infected women have a higher likelihood of developing persistent high-risk human papillomavirus (HPV) infection, precancer, and invasive cervical cancer than seronegative women. Although highly effective primary and secondary prevention strategies are currently available, they remain inaccessible to the vast majority of women. Because of their simplicity and affordability, see- and-treat cervical cancer screening modalities have the potential to substantially improve women’s access to cancer prevention, as well as to create much needed infrastructure for future molecular-based cervical screening and HPV vaccination programs. Additional data addressing the effectiveness of see-and-treat approaches for HIV-infected women are urgently needed. Studies informing best practice guidelines on when to start, when to stop, and how frequently to screen HIV-infected women within the see-and-treat paradigm would be of great value.